Cross-scale analysis of diversification processes in fuelwood use in three contrasting ecoregions of Argentina (Chaco, Pampa and Patagonia): the role of exotic species in subsistence - Jiménez-Escobar, N. David; Doumecq, María Belén; Morales, Daniela; Ladio, Ana H. (Ethnobiology and Conservation, 2021)
Fuelwood is one of the main sources of energy for rural populations in many environments and ecosystems. However, little research has been done on the diversification processes associated with the use of woody plants for fuel (UWPF). This study was carried out in rural communities of three eco-regions of Argentina (the phytogeographical provinces of Chaco, Pampa and Patagonia). Open and semi-structured interviews were performed in 72 households, focusing on the current richness of fuelwood, supply strategies and gathering sites. The biogeographical origin of the mentioned species was established, and the pressure of use on fuel wood was evaluated indirectly. The results were analysed qualitatively and quantitatively. A total of 78 species was recorded, of which 51 were native and 27 exotic. Gathering is the most common supply strategy in all the ecoregions studied, fuelwood being obtained mainly in sites with little human intervention. Pressure of use did not vary between native and exotic species. A generalized linear model showed that the use of native versus exotic species varied according to the ecoregion and the level of human intervention in the supply area, while acquisition strategies were similar for both native and exotic species in all eco-regions. Each region presented different use patterns, but the areas with most human intervention were always used to gather exotic plants. In line with our hypothesis, the diversification processes in UWPF varied according to ecoregion, each area having intrinsic characteristics associated with its history. The exotic species currently used as fuel wood increase the repertory of plants recognised and used by the local population.